(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Face of Global Banking is undergoing a transition. Banking is now a global issue. Reforms in the financial sector, covering banking, insurance, financial markets, trade, taxation etc. have been a major catalyst in strengthening the fundamentals of the Indian economy. The reform measures have brought about sweeping changes in this critical sector of the Indian’s economy. Banking in India is generally fairly mature in terms of supply, product range, and reach-even though reach in rural India still remains a challenge for the private sector and foreign banks in the year 2007. The broad objective of the financial sector reform has thus been to create a viable and efficient banking system. Improvements in the growth rate can be effected through three, not necessarily mutually exclusive channels: improving productivity of capital, through investments in human capital and raising total factor productivity (TFP).Indian economy has been recording impressive growth rates since 1991. The main thrust of the financial sector reforms has been the creation of efficient and stable financial institutions and development of the markets, especially the money and government securities market. In addition, fiscal correction was undertaken and reforms in the banking and external sector were also initiated.The financial sector in India – banking, capital markets, insurance, mutual funds, etc. - has changed during the decade of reform of the nineties. Although many improvements have been effected, this paper argues that the scope of many of these changes has been relatively narrow and predominantly mechanistic. It is not surprising, therefore, that the outcomes of these actions have not been as far-reaching as required. While the sector is probably more robust than at the beginning of reforms, it is still susceptible to inefficiencies engendered inter alia by the blunted incentives associated with large public sector involvement in the sector, institutional rigidities and regulatory forbearance.